Teaching English for Specific Purpose Through a Book Entitled “Communicating at Work: Principles and Practices for Business and the Professions” - Ariani Rosadi; Lubis Hermanto (Departement of Mathematics Education, 2023)
This study aims to investigate the experience of teaching ESP (English for Specific Purpose) courses for students of the communication science study program at Mbojo Bima University. Dominantly, ESP teaching uses an English book entitled